2016
DOI: 10.1371/journal.pone.0166560
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Alleviates Heart Failure by Inactivating ERK1/2/GATA4 Signaling Pathway after Pressure Overload in Mice

Abstract: BackgroundHeart failure(HF) is a dangerous disease that affects millions of patients. Radix Salvia is widely used in Chinese clinics to treat heart diseases. Salvianolic acid B(SalB) is the major active component of Radix Salvia. This study investigated the mechanisms of action and effects of SalB on HF in an experimental mouse model of HF.MethodsWe created a mouse model of HF by inducing pressure overload with transverse aortic constriction(TAC) surgery for 2 weeks and compared among 4 study groups: SHAM grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…These observations thus suggest the potential effects of Sal-B in the treatment of heart failure, which develops as an automatic response to pathological cardiac remodeling. In agreement with this notion, a recent study has demonstrated that Sal-B alleviates heart failure induced by pressure overload [297] . Therefore, Sal-B holds promise for cardioprotection against heart failure but requires confirmation in more experimental and clinical studies.…”
Section: Protective Effects Of Sal-a Against Cardiac Remodelingsupporting
confidence: 52%
“…These observations thus suggest the potential effects of Sal-B in the treatment of heart failure, which develops as an automatic response to pathological cardiac remodeling. In agreement with this notion, a recent study has demonstrated that Sal-B alleviates heart failure induced by pressure overload [297] . Therefore, Sal-B holds promise for cardioprotection against heart failure but requires confirmation in more experimental and clinical studies.…”
Section: Protective Effects Of Sal-a Against Cardiac Remodelingsupporting
confidence: 52%
“…Salvianolic acid B (SalB, Figure 1 ) the most abundant and bioactive member of polyphenolic compounds derived from the root of Salvia miltiorrhiza (Danshen) and has been used widely and successfully in Traditional Chinese Medicine clinical practices for cardio-cerebral vascular diseases ( Wang et al, 2013 ; Yu et al, 2016 ). Moreover, SalB is reported to have several therapeutic effects on obesity, insulin resistance and type 2 diabetes ( Wang et al, 2014 ; Huang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 The cardioprotective effects of Danshen may result from its components, including tanshinone IIa, 10 cryptotanshinone, 11 tanshinone VI, 12 danshensu, 13 salvianolic acid A, 14 and salvianolic acid B. 15 It has been shown in dogs 10 and rats 16 that tanshinone IIa ameliorates cardiac infarction induced by left anterior descending artery ligation through suppression of inflammation. Moreover, dihydrotanshinone I (DHTS), which is one of the major lipidsoluble constituents of Danshen, 17 has been shown to possess an anti-atherosclerosis effect in ApoE −/− mice.…”
Section: Introductionmentioning
confidence: 99%